Pertinence of the curriculum of the Degree of Nursing at the University of Costa Rica with the socio-labor context - Rojas Valenciano, Ligia (2013)
The objective of this paper is to present the results of educational research which analyzed the pertinenceof the curriculum in the context of socio-labor Bachelor in Nursing at the University of Costa Rica. Thepopulation consisted of the graduates and public and private institutions of generating 2008 and the employingbodies where graduates worked. We applied a simple probabilistic sample was chosen employing bodies wheresix institutions were working the graduates and selected in the sample. We analyzed three dimensions: graduatetraining, performance in nontraditional fields and significance of industrial action in the person's attention. Tocollect data, a questionnaire was structured and semi-structured interviews with key informants. The study foundthat the educational proposal for the Bachelor in Nursing at the University of Costa Rica, is closely pertinence tothe socio-labor. However, the educational process must be constantly revised, updated and improved according tothe proposals that emerge over time for the students to ensure that your training will meet the requirements inhealth, social and employment. We conclude that there is a strong coherence between training and jobperformance fields and graduated from. However, more time is required for the development of learningexperiences in the course modules and care management, and improve internal to everyone adequacy andappropriateness of such experiences, in order to be in constant improvement of educational provision.